PEMANFAATAN MEDIA CANVA DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) PADA PEMBELAJARAN IPAS DI SD (JS (JURNAL SEKOLAH), 2024)
Abstract: The purpose of this study is to ascertain how the use of Canva media in conjunction with a Culturally Responsive Teaching (CRT) strategy affects student learning results in science classes V and science topics at SDN Sawojajar 01. Teachers have a problem when creating learning materials that meet the requirements of students from a variety of backgrounds. In this study, a nonequivalent control group design is employed in conjunction with a quasi-experimental quantitative technique. Pretest-posttest multiple choice questions are used in the study instrument. It was shown that (0.00